Bridging Dealumination and Desilication for the Synthesis of Hierarchical MFI Zeolites. (1st September 2017) - Yang, Shitu; Yu, Chenxi; Yu, Lili; Miao, Shu; Zou, Mingming; Jin, Changzi; Zhang, Dazhi; Xu, Longya; Huang, Shengjun
Abstract: The rational design of zeolite‐based catalysts calls for flexible tailoring of porosity and acidity beyond micropore dimension. To date, dealumination has been applied extensively as an industrial technology for the tailoring of zeolite in micropore dimension, whereas desilication has separately shown its potentials in the creation of mesoporosities. The free coupling of dealumination with desilication will bridge the tailoring at micro/mesopore dimensions; however, such coupling has been prevailingly confirmed as an impossible mission. In this work, a consecutive dealumination–desilication process enables the introduction of uniform intracrystalline mesopores (4–6 nm) into the microporous Al‐rich zeolites. The decisive impacts of steaming step have been firstly discovered. These findings revitalize the functions of dealumination in porosity tailoring, and stimulate the pursuit of new methods for the tailoring of industrially relevant Al‐rich zeolites. Abstract : Zwei Prozesse verschmolzen : Ein konsekutiver Dealuminierungs‐Desilicierungs‐Prozess ermöglicht es, einheitliche intrakristalline Mesoporen (4–6 nm) in mikroporöse Al‐reiche MFI‐Zeolithe einzuführen. Die Entwicklung einer hierarchischen Porosität hängt von der Dampftemperatur, der Teilchengröße und dem Zusammenwirken der Bedingungen beider Prozesse ab.